Republic of Slovenia : Technical Assistance Report-Contingency Planning and Crisis Management. (IMF Staff Country Reports; Country Report ;, 2016)
This Technical Assistance report makes recommendations regarding introduction of an effective framework for contingency planning and crisis management, including bank resolution and deposit guarantees, in Slovenia. It is recommended that a communication plan and strategy be developed, both within the Bank of Slovenia and at the national level, to speak with one voice during financial crises. The members of Co-ordination Group/Financial Stability Board (CG/FSB) must harmonize their efforts to carefully coordinate information, provide consistent communication to the public, and ensure that they use the same facts and assumptions. Whenever a crisis appears forthcoming, CG/FSB members should plan to deliver a media statement providing information in a constructive manner to reassure the public.